Effectiveness of Science-Technology-Society (STS) approach on students' learning outcomes in science education: Evidence from a meta-analysis - Dharel Acut; Ronilo Antonio (OmniaScience, 2023)
Scientific literacy development significantly impacts real-world outcomes, leading to scrutiny of instructional approaches for global reform in science education. This study aimed to determine the efficacy of the Science-Technology-Society (STS) approach in improving students' scientific learning outcomes. A quantitative research design, using meta-analysis guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol, was used to determine the effect sizes of previous studies on the STS approach's effectiveness in science learning and teaching. The study analyzed 16 effect sizes from 14 empirical studies from January 2017 to September 2022 using Harzing's Publish or Perish application and Comprehensive Meta-Analysis (CMA) software. Results showed that the STS approach significantly and positively impacts students' learning outcomes (g = 1.882), particularly psychomotor skills, affective domain, and cognitive skills. Moderator analysis showed that STS is an effective teaching strategy that yields similar positive results regardless of the assessed learning outcomes. The findings demonstrated that the STS approach facilitates students' development of scientific knowledge, skills, and mindset to innovate for real-world problems. These findings provided empirical information that are essential for learning analytics applications in predicting learners' performance and diagnosing instructional practices. Implications for future research and practice, as well as addressing publication bias, are highlighted in order to maximize the benefits of the STS approach in science education.